Synthesis, Growth and Characterization of Glycine Ammonium Bromide: A potential NLO material. (2019) - Sankar, K.; Rajasekaran, R.; Vetrivelan, V.
Abstract: A novel semi organic material of glycine ammonium bromide (GAB) has been synthesized and effectively grown by the slow evaporation method. The grown crystals have been exposed to various characterization techniques such as single crystal / powder XRD, UV- Vis- NIR absorption, FTIR, thermal analysis and powder SHG measurements. Sensible clear GAB crystals were obtained in an exceedingly time span of 25 days. The full grown crystals were thermally stable up to 281˚C. The GAB crystal exhibits SHG efficiency of about 1.80 times than that of KDP. On the whole the properties advise that the present material may be an efficient candidate for NLO device applications.